Systemic Intertextuality. A Morphogenetic Perspective - Burzyński, Tomasz (Text Matters: A Journal of Literature, Theory and Culture, 2020)
If late modern literary production is structured by any principles rendering order to the otherwise nebular character of the process, this is the idea of intertextuality that paves the way for the dissolution of well entrenched structures, literary conventions and institutionalized canons. By fostering and facilitating the erosion of boundaries between elite and popular culture, mechanisms of intertextuality show that literature is not only a fixed collection of texts, but also a dynamic social system including structured practices of production and reception together with their institutional, cultural and technological determinants. The paper aims to provide a sociologically-oriented model of intertextual relations taking place within the social system of literature. In this context, circulation, dissemination, and recycling of literary motifs is viewed from a perspective of morphogenetic processes which result in the structural elaboration and systemic change due to the mobilization of social, cultural, and economic capitals in an effort to alter pre-existent practices of signification. Consequently, literature is discussed as an intertextual system in statu nascendi, a sphere of social practices that knows no sense of institutional boundaries or structural constraints.